Parco Urbano: Università degli Studi di Pisa - Heliopolis 21 (AND Rivista di architetture, città e architetti, 2019)
The main objective of the intervention, in the historical centre of Pisa, has been the transformation of the spaces between the existing historic buildings into a real urban park, which acts as connective tissue between the various university buildings that overlook it.